2022
DOI: 10.5187/jast.2022.e39
|View full text |Cite
|
Sign up to set email alerts
|

Silybum marianum seed extract supplementation positively affects the body weight of weaned piglets by improving voluntary feed intake

Abstract: This study was conducted to evaluate the effects of dietary supplementation of Silybum marianum seed (SMS) extract on the growth performance, nutrient digestibility, fecal noxious gas emission, and hematology parameters in weaned piglets. A total of 120, 21-day-old weaned piglets ([Yorkshire × Landrace] × Duroc) were randomly assigned to 3 groups based on the average initial body weight (6.46 ± 0.45 kg). There were 8 replicate pens per treatment and 5 pigs (mixed sex) per pen. The experimental period was 42 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
2
3
0
Order By: Relevance
“…These results are consistent with the findings of Dang et al (2022), who reported that Silybum marianum seed extracts at concentrations of 0%, 0.05%, and 0.1% had a linear positive effect on both ADG and ADFI in weaning piglets. Similarly, Grela et al (2020) observed that adding 6% milk thistle seeds to the diet increased BW, ADG, and ADFI of pigs weighing between 25 and 115 kg.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These results are consistent with the findings of Dang et al (2022), who reported that Silybum marianum seed extracts at concentrations of 0%, 0.05%, and 0.1% had a linear positive effect on both ADG and ADFI in weaning piglets. Similarly, Grela et al (2020) observed that adding 6% milk thistle seeds to the diet increased BW, ADG, and ADFI of pigs weighing between 25 and 115 kg.…”
Section: Discussionsupporting
confidence: 93%
“…However, nutrient utilisation was not affected, which was in line with the findings of Dang et al (2022). However, it is worth noting that Shanmugam et al (2022) found that dietary MS supplementation (0.04% and 0.06%) improved nutrient utilisation in broilers.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Mohankumar et al [ 19 ] showed no influence on fecal gas emission when supplementing 0.05% AJE to the finishing pigs diets. Moreover, medicinal plant extracts in weaning pigs diets failed to affect both the nutrient digestibility as well as fecal gas emissions [ 34 ]. The lower dose of AJE used in the study may be responsible for this result.…”
Section: Discussionmentioning
confidence: 99%
“…It has large amounts of vitamins of group B, necessary for the regulation of fat metabolism, nutrition of the cardiac muscle, nervous system, skin, eyesight organs, and also fat-solving vitamins -А, F, E and К. Also, the seeds contain the following macroelements (mg/g): potassium -9.2, calcium -16.6, magnesium -4.2, ferrum -0.08; microelements (µg/g): cuprum -1.16, manganese -0.10, zinc -0.71, chromium -0.15, selenium -22.9, iodine -0.09, boron -22.4 (Martyshuk et al, 2020(Martyshuk et al, , 2022Dang et al, 2022). Fruits of Silybum marianum (L.) Gaertn.…”
Section: Discussionmentioning
confidence: 99%